An Extensive Catalog of Early-type Dwarf Galaxies in the Local Universe: Morphology and Environment - Sanjaya Paudel; Suk-Jin Yoon; Jaewon Yoo; Rory Smith; Daya Nidhi Chhatkuli; Rajesh Kumar Bachchan; Binil Aryal; Binod Adhikari; Namuna Adhikari; Amrit Sedain; Sharup Sheikh; Sarashwati Dhital; et al. (The Astrophysical Journal Supplement Series, 2023)
We present an extensive catalog of 5405 early-type dwarf (dE) galaxies located in the various environments, i.e., clusters, groups, and fields, of the local universe ( z < 0.01). The dEs are selected through visual inspection of the Legacy survey’s g – r – z combined tricolor images. The inspected area, covering a total sky area of 7643 deg ^2 , encompasses two local clusters (Virgo and Fornax), 265 groups, and the regions around 586 field galaxies of M _K < −21 mag. The catalog aims to be one of the most extensive and publicly accessible collections of data on dEs, despite its complex completeness limits, which may not accurately represent its statistical completeness. The strength of the catalog lies in the morphological characteristics, including nucleated, tidal, and ultradiffuse dEs. The two clusters contribute nearly half (2437 out of 5405) of the dEs, and the 265 groups contribute 2103 dEs. There are 864 dEs in 586 fields, i.e., ∼1.47 dEs per field. Using a standard definition commonly used in literature, we identify 100 ultradiffuse galaxies (UDGs), which compose ∼2% of the dE population. We find that 40% of our sample dEs harbor a central nucleus, and among the UDG population, a majority (79%) are nonnucleated. About 1.3% of dEs suffer from ongoing tidal disturbance by nearby massive galaxies, and only 0.03% show a sign of recent dwarf–dwarf mergers. The association between dEs and their nearest bright neighbor galaxies suggests that dEs are more likely created where their neighbors are non-star-forming ones.